Sistem Skor Baru untuk Memprediksi Kejadian Perdarahan pada Pasien Infark Miokard Akut dengan Elevasi Segmen ST yang Dilakukan Intervensi Koroner Perkutan Primer - Wisnu A Widodo; Sunarya Soerianata; Andang H Joesoef; Ganesya M Harimurti (The Indonesian Heart Association, 2013)
Background Acute myocardial infarction still become one of the leadingmortality cause in the world. Among these patients, ST elevation myocardialinfartion (STEMI) has the greatest mortality rate among other type ofMyocardial Infarction. When a myocard infarct patient have bleeding events,mortality rate greatly increased. Up until now, there is no specific bleedingrisk assessment tool to predict bleeding events in STEMI patient.Methods A retrospective cohort study, done in National Cardiovascular CenterHarapan Kita, Jakarta in STEMI patients underwent Primary PercutaneousCoronary Intervention (PPCI). Bleeding event was defined according to definitionby Bleeding Academic Research Consortium (BARC) – European Societyof Cardiology, 2011. Categories for data obtained was basic characteristics,clinical examinations, initial therapies, lab results, x-ray, PPCI procedures, andin hospital treatments. Statistical analysis was done using multivariat analysisusing logistic regression method and then converted to a scoring system.Results 579 sampels fit the inclusion and exclusion criteria. Bleeding eventoccured in 42 patients (7.3%). Indonesia bleeding score (Range 1-100) wascreated by assignment of variables that included in the final model accordingto their Odds Ratio (OR) values. Those variables are: female gender(OR 2.91, CI 1.23-6.91), Killip class 3 / 4 (OR 5.64, CI 2.27-14.03), Age ?62 y.o (OR 2.19, CI 1.00-4.83), White blood cell >12.000 (OR 2.12, CI0.95-4.73), Creatinine >1.5 (OR 2.17, CI 0.95-4.96), Body Mass Index ?25 (OR 1.71, CI 0.83-3.51), Multiple coronary lesion (OR 1.95, CI 0.83-4.54), Femoral access (OR 2.33, CI 0.77-7.01), and TPM implantation (OR3.21, CI 1.28-8.07). These variabels was converted into two type of scoringsystem. The INA-1 contains all of the variables, and INA-2 minus variablesrelated to interventional result and procedures.Conclusion Indonesia bleeding score quantifies risk for in-hospital bleedingevent in STEMI patients underwent PPCI, which enhances baseline riskassessment for STEMI care.